Isobaric-isothermal molecular dynamics computer simulations of the properties of water-1,2-dimethoxyethane model mixtures - Gujt, J.; Dominguez, H.; Sokolowski, S.; Pizio, O. (Condensed Matter Physics, 2017)
Isothermal-isobaric molecular dynamics simulations have been performed to examine a broad set of properties of the model water-1,2-dimethoxyethane (DME) mixture as a function of composition. The SPC-E and TIP4PEw water models and the modified TraPPE model for DME were applied. Our principal focus was to explore the trends of behaviour of the structural properties in terms of the radial distribution functions, coordination numbers and number of hydrogen bonds between molecules of different species, and of conformations of DME molecules. Thermodynamic properties, such as density, molar volume, enthalpy of mixing and heat capacity at constant pressure have been examined. Finally, the self-diffusion coefficients of species and the dielectric constant of the system were calculated and analyzed. Для того, щоб дослiдити широкий набiр властивостей модельних сумiшей вода-1,2-диметоксиетан (DME) в залежностi вiд концентрацiї, проведено комп’ютерне моделювання методом молекулярної динамiки в iзобарично-iзотермiчному ансамблi. Для води застосовано моделi SPC-E i TIP4P-Ew, а для DME — модифiковану модель TraPPE. Нашим основним завданням було дослiдити тенденцiю поведiнки структурних властивостей в термiнах радiальних функцiй розподiлу, координацiйних чисел та чисел водневих зв’язкiв мiж молекулами рiзних сортiв, а також конформацiї молекул DME. Вивчено термодинамiчнi властивостi, такi як густина, молярний об’єм, ентальпiя змiшування i питома теплоємнiсть при постiйному тиску. Накiнець, обчислено i проаналiзовано коефiцiєнти самодифузiї сортiв i дiелектричну сталу системи.